Development for water, food and nutrition in a competitive environment — How NGOs and CSOs are reshaping traditional farmer irrigation advisory services. (17th April 2020) - Unver, Olcay; Kay, Melvyn; Chavva, Konda; Amali, Amali Abraham; Pek, Eva; Salman, Maher
Abstract: In spite of the 30% increase in the food supply since 1961, significant changes are anticipated over the coming decades that will increase the challenges facing smallholders. Climate change, rapidly growing population and increasing pollution all add to the risks of water and food security. This is happening at a time when water resources management is shifting away from government planning and control to a more adaptive and flexible model involving more stakeholders, whereby farmers and smallholders are increasingly involved in decision‐making and governance of water resources. Many governments, however, continue to look to their smallholders to increase food production and to find ways to produce more with less. Farmers, thus, will need to find new ways of learning and rely more on their own resources, on the private sector and on support from civil society organizations and non‐governmental organizations. This paper examines the changing nature of farmer support services, focusing on the role played by emerging non‐institutional actors. As water becomes the limiting resource for food production, it is crucial to understand how food markets are growing and can incentivize smallholders to produce more, and critically, how farmers are finding new ways of acquiring the knowledge and expertise they need. Résumé: Malgré l'augmentation de 30% de l'approvisionnement alimentaire depuis 1961, des changements importants sont prévus au cours des prochaines décennies, ce qui augmentera les défis auxquels sont confrontés les petits exploitants. Le changement climatique, la croissance rapide de la population, l'augmentation de la pollution, s'ajoutent tous aux risques de l'eau et de la sécurité alimentaire. Cela se produit à un moment où la gestion des ressources en eau s'éloigne de la planification et du contrôle gouvernementaux vers un modèle plus adaptatif et flexible impliquant plus de parties prenantes, dans lequel les agriculteurs et les petits exploitants sont de plus en plus impliqués dans la prise de décision et la gouvernance des ressources en eau. Cependant, de nombreux gouvernements continuent de se tourner vers leurs petits exploitants pour augmenter la production alimentaire et trouver des moyens de produire plus avec moins. Les agriculteurs devront donc trouver de nouvelles façons d'apprendre et s'appuyer davantage sur leurs propres ressources, sur le secteur privé et sur le soutien des organisations de la société civile et des organisations non gouvernementales. Cet article examine la nature changeante des services de soutien aux agriculteurs, en se concentrant sur le rôle joué par les acteurs non institutionnels émergents. Alors que l'eau devient la ressource limitante pour la production alimentaire, il est essentiel de comprendre comment les marchés alimentaires se développent et peuvent inciter les petits exploitants à produire davantage, et, surtout, comment les agriculteurs trouvent de nouvelles façons d'acquérir les connaissances et l'expertise dont ils ont besoin.